1997
DOI: 10.1007/bf01461736
|View full text |Cite
|
Sign up to set email alerts
|

Missed fractures on emergency room ankle radiographs: An analysis of 433 patients

Abstract: The purpose of this study was to review fractures and radiographic abnormalities that are detectable, but often overlooked, on a standard ankle radiographic series. We carried out a retrospective review of 556 consecutive ankle radiographic series obtained between June 1, 1995, and May 31, 1996. From this population, 433 complete ankle radiographic series on patients with suspected trauma were selected. The original radiologist's interpretation was compared to a two. step "gold standard" interpretation, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Of these extra-articular fractures, the ones situated at the anterior aspect of the calcaneus are the most common. The mechanism of injury as described by Brandser et al [1] is adduction with the foot in equinus position. They also reported higher incidence in women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of these extra-articular fractures, the ones situated at the anterior aspect of the calcaneus are the most common. The mechanism of injury as described by Brandser et al [1] is adduction with the foot in equinus position. They also reported higher incidence in women.…”
Section: Discussionmentioning
confidence: 97%
“…The calcaneus is the most commonly injured bone of the foot. Although they comprise only 25 % of all calcaneal fractures, fractures of the extra-articular type are more difficult to diagnose according to Brandser et al [1]. Of these extra-articular fractures, the ones situated at the anterior aspect of the calcaneus are the most common.…”
Section: Introductionmentioning
confidence: 98%
“…The primary intent of our study was to analyze the feasibility of using AI techniques for identifying ankle fractures. This was achieved using the following criteria: (1) The model should be able to correctly detect minor fractures as well as major fractures; (2) the performance of the model should either equal or surpass human diagnosis. We concluded that the study, in its present capacity, fell short on both aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The ankle consists of 3 bones (the tibia, fibula, and talus), 2 joints (ankle and syndesmosis), and 3 sets of ligaments (medial, lateral, and syndesmotic). Owing to the complex structure of the ankle, fractures associated with it are often difficult to identify, raising the rate of misdiagnosis to nearly 4.2% in the ED [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Brijs [13] suggested that these small fractures are caused by avulsions at the insertion site of the bifurcate ligament. Usually the avulsion is an isolated fracture and avulsed fragments resolved within a few months [11,13,29,55]. Treatment is usually conservatively consisting of 2 weeks non-weight bearing, bandaging and early active motion exercises, and outcome is favourable in all patients [13,29,55].…”
Section: Anterior Avulsion Fracturesmentioning
confidence: 99%